The Financial Problems of Tsangaya System of Education and its Effects on Almajiri in Potiskum Yobe State Nigeria - Ibrahim Dahiru Idriss; Nura Abubakar Gwadabe (International Journal of Emerging Issues in Islamic Studies, 2021)
Tsangaya system of education, generally called traditional Qur’anic school has been in existence earlier to the British colonization as a source of moral and scholastic training of the Muslim dominated societies in the northern part of Nigeria. The study aims to examine the financial challenges of the Tsangaya system of education in Potiskum area of Yobe State and to examine its effect of the Almajiri. The system which provides, essentially, basic Qur’anic education has contributed tremendously in promoting Qur’anic education, inculcating self-discipline, spiritual growth of Muslim individuals and the communities. The system is also facing several financial related problems which has effected Almajiri (students), teachers and the school as well. Majority of Almajiri (students) hailed from poor families and were sent to Tsangaya schools as Almajiri. Due to the indigent background of their families, the Almajiri do not have the means to support their studies. The lack of the required facilities by the Tsangaya schools for better teaching and learning such as provision of food, accommodation and other basic necessities, has affected the Almajiri. Therefore, this study employed a qualitative approach that entails the techniques of documentation and interviews in collecting data while inductive approach of thematic analysis was utilized for data analysis. The findings revealed that, the system of Tsangaya education were in existence in Potiskum area for a decades and it has affected the lives of the Almajiri in various spheres of lives and its lingering financial problems brought a negative effect to the socio- economic wellbeing of the Almajiri in the area.